2018
DOI: 10.1089/dia.2018.0202
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Analysis of 3-Month Real-World Glucose Data After the MiniMed 670G System Commercial Launch

Abstract: Real-world data from the first 3141 patients who completed 3 months of SmartGuard™ Auto Mode-enabled MiniMed™ 670G system use during the MiniMed 670G System Commercial Launch are reported. CareLink™ system data uploaded by real-world patients in the Commercial Launch from March 17, 2017 to December 31, 2017 were deidentified and analyzed. Comparisons of overall and night (10:00 PM-07:00 AM) time spent below, within, and above target glucose range (TIR) (70-180 mg/dL) between the baseline Manual Mode and closed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
82
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(86 citation statements)
references
References 6 publications
3
82
0
1
Order By: Relevance
“…Likewise, each 8.6‐h increase in Auto Mode time per day was associated with 5% more TIR. These findings are consistent with previous 670G trials that demonstrated improvements in glycaemia, including increased TIR and reduction in HbA1c . The ability of automated insulin delivery to improve glycaemia may particularly benefit adolescents and young adults, who have mostly struggled with meeting therapeutic targets.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Likewise, each 8.6‐h increase in Auto Mode time per day was associated with 5% more TIR. These findings are consistent with previous 670G trials that demonstrated improvements in glycaemia, including increased TIR and reduction in HbA1c . The ability of automated insulin delivery to improve glycaemia may particularly benefit adolescents and young adults, who have mostly struggled with meeting therapeutic targets.…”
Section: Discussionsupporting
confidence: 90%
“…This automated insulin delivery system provides insulin using either its HCL “Auto Mode” feature or an open‐loop “Manual Mode”. The 670G pivotal trial and larger real‐world studies show that glycaemia improves after initiation of Auto Mode in both paediatric and adolescent populations . These improvements include increased time in range (TIR, defined as sensor glucose, SG, 70–180 mg/dL), reduced glycaemic variability and lower haemoglobin A1c (HbA1c) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Time in target range increased from 64% to >70%, time below target range of <70 mg/dL (<3.9 mmol/L) decreased by 30% (from 2.6% to 2.0%), and CV decreased from 33% to 30% in adult subjects . The real‐world experience in over 3000 patients using the device after its commercial launch in the US has mirrored the pivotal study results . The next steps in AP system development will involve better algorithms that include meal detection and contextual information and, most importantly, improved insulins pharmacokinetics.…”
Section: Non‐hba1c Metrics Help Understand the Benefits Of Advanced Dmentioning
confidence: 96%
“…In between times, the pump regulates insulin delivery with the aim of keeping the glucose in the target range. This system has shown favourable outcomes in real‐world observational data with over 3141 users in the USA with a mean time in range (3.9–10mmol/L) of 73% during automode …”
Section: Introductionmentioning
confidence: 99%